PENGARUH KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN JOGLO BAR & RESTAURANT DI CANDIDASA, KARANGASEM - Putri Anggreni; I Wayan Budiasa (STIMI Handayani Denpasar, 2022)
Leadership has a very important meaning for the smooth running of a company or organization, because with a leadership style that is carried out in a company that is able to bring the company to get predetermined goals. Likewise, the employee's work motivation has a very important meaning for the survival of the company, with high work motivation, it will cause a high sense of concern for the achievement of company goals. The purpose of this study was to find out how much influence leadership has on employee work motivation at Joglo Bar & Restaurant. The data collection method used, namely through observation, interviews, recording documents, and questionnaires. The data analysis techniques used are simple linear regression analysis, product moment correlation analysis, determination analysis, and product moment correlation coefficient t-test. Based on the results of the study, the results obtained there was a positive influence between increasing leadership on the work motivation of employees at Joglo Bar & Restaurant. Determination analysis showed that the influence of leadership by 65.6% on the work motivation of employees, while the remaining 34.4% was influenced by other factors that were not described in this study. Thus, it can be suggested to the company, especially the management and leadership of Joglo Bar & Restaurant to continue to develop their role as a leader in order to achieve the company's goals.